PBOSPECTS FOR CLINICAL APPLICATION OF THE CURRENT ANTI-INFLAMMATORY DRUG MELOXICAM (AMELOTEX) - M S Eliseev; M S Eliseyev (Современная ревматология, 2008)
The paper presents data on the effectiveness, safety, tolerance, major mechanisms of action, and prospects for clinically using meloxicam, a current selective nonsteroidal anti-inflammatory drug, against cyclooxygenase-2. It describes the advantages of meloxicam for injections, which begins acting promptly and shows an adequate long analgesic effect.